Outcome of implementing Surgical Safety Checklist in Pediatric Surgery in Tertiary Level hospital (Nepal Medical College Journal, 2021)
The World Health Organization (WHO) implemented the Surgical Safety Checklist (SSCL) as a part of Safe Surgery Saves Lives campaign. Even after 12 years of implementation of WHO SSCL, available literature is still lacking from developing countries, where the potentially greatest impact could have been observed. A prospective randomized controlled trial done in Tertiary level hospital from September 2018 – February 2020 enrolled pediatric patients aged 0 day to 15 years. The patients were randomly allocated into groups by lottery as Group A - control and Group B – Intervention group. Group A was given the basic pre-operative care. Group B were enrolled in the safety checklist. The data were collected in the printed forms and analyzed. The patients were followed for surgical site infections (SSI). Compliance of the safety checklist was assessed with completion of the checklist fully or partially. Total cases enrolled were 310 with 155 in each group. Age of patients ranged from 1 day to 15 years. SSI was present in 35 patients in group A and 29 patients in group B. The Outcome of implementation of SSC on appearance of SSI was not significant. SSI was decreased on checklist implementation with OR of 0.78 (95% CI 0.45 – 1.37). Outcome of SSC compliance shown by OR was 0.39 (95% CI 0.15 – 0.99). Use of SSCL decreases the postoperative complications and improves the outcome. Compliance is the key to success of the implementation of the checklist.